Disinfection of water by singlet oxygen - Jiménez Hernández, Emilia (2010)
This paper provides an overview of research on water disinfection procedures based on the use of singlet oxygen, bactericidal species that can be generated catalytically by photosensitization. The presentation begins with a review of currently available treatments for water disinfection, highlighting the advantages and disadvantages or limitations that characterize some of them. Are introduced, then the properties of singlet oxygen and its reactivity to the molecules that comprise biological systems because it lies in the germicidal action of this reactive oxygen species. Having described the process of generation of singlet oxygen by photosensitization, showing various structures of molecules commonly used as singlet oxygen photosensitizers. Finally, after discussing some aspects of the research published by various authors on the use of singlet oxygen as a disinfectant, is currently present studies we conducted in our research group of the Laboratory of Applied Photochemistry (Universidad Complutense de Madrid, Spain). The research into SOLWATER project, funded by the European Union, the general had with objective of developing new methods of disinfecting water, using sunlight to generate the kind germicide by photosensitization, resulting economic, safe and friendly environment.